analysis analysis of social media management strategy @tallethacosmetic through Instagram media: analisis strategi pengelolaan media sosial @tallethacosmetic melalui media instagram - Maharani, Defitri; Mareta Puri Rahastine (SM Institute, 2025)
Social media has now become one of the most effective promotional tools in supporting business activities, especially in the rapidly evolving digital era. Instagram, as a visual-based social media platform, holds great potential in reaching consumers, particularly among young people. This study aims to analyze the Instagram social media management strategy of the @Tallethacosmetic account, a retail store specializing in cosmetics and fashion located in South Tambun, Bekasi. The research uses a descriptive qualitative approach with data collection methods including semi-structured interviews, observation, and documentation. Data analysis refers to Chris Heuer’s 4C theory, which includes Context, Communication, Collaboration, and Connection. The results show that the @Tallethacosmetic account creates content that aligns with the characteristics of its audience—women aged 18– 30—focusing on bright visuals and communicative language. Two-way communication is actively carried out through Instagram features such as stories, comments, polls, and direct messages. Collaborations with micro-influencers have been initiated, although not on a regular basis. The study concludes that an appropriate and consistent social media strategy can increase engagement, expand promotional reach, and build a positive brand image in the eyes of consumers.